Prevalence of Constipation in Elderly and Its Association With Dementia and Mild Cognitive Impairment: A Cross-Sectional Study - Wang, Fei; Fei, Min; Hu, Wen-Zheng; Wang, Xiao-Dan; Liu, Shuai; Zeng, Yan; Zhang, Jin-Hong; Lv, Yang; Niu, Jian-ping; Meng, Xin-ling; Cai, Pan; Li, Yang; et al. (Frontiers in Neuroscience, 2022)
Background: Constipation and dementia have similar epidemiological characteristics. Changes in intestinal flora and characteristics of the brain-gut axis play roles in the pathogeneses of the two diseases, suggesting that there may be a close connection between the two. Most of the studies on constipation in dementia patients have focused on the population with α-synucleinopathies (Parkinson disease dementia [PDD], dementia with Lewy bodies [DLB]). Few studies have reported the prevalence of constipation in all-cause dementia and mild cognitive impairment (MCI) populations. Objective: To assess the prevalence of constipation in patients with all-cause dementia, MCI and MCI subtypes and to explore the association between chronic constipation with dementia, MCI and MCI subtypes. Methods: From May 2019 to December 2019, we conducted a population-based cross-sectional survey. A total of 11,743 participants aged 65 or older from 9 cities in China were surveyed. Participants underwent a series of clinical examinations and neuropsychological measurements. Chronic constipation, dementia, MCI and MCI subtype were diagnosed according to established criteria through standard diagnostic procedures. Results: The overall age- and sex-adjusted prevalence of chronic constipation in individuals aged 65 years and older was 14.8% (95% CI, 14.6-15.0). The prevalence rates of chronic constipation were19.2% (95% CI, 17.3-21.0), 19.1% (95% CI, 16.8-21.5), 14.4%(95% CI, 12.8-15.9), and13.8%(95% CI, 13.0-14.6) in the dementia, nonamnestic (na)-MCI, amnestic (a)-MCI and normal cognition populations, respectively. Multivariate logistic regression analysis showed that chronic constipation was a risk factor for dementia (p = 0.0.032, OR = 1.18, 95% CI: 1.02-1.38) and na-MCI (p = 0.003, OR = 1.30, 95% CI: 1.09-1.54). Conclusion: The present study found a high prevalence of chronic constipation in elderly individuals in China, especially those with dementia and na-MCI. Chronic constipation is a risk factor for dementia and na-MCI.